Using DEA and Malmquist Productivity Index to Analyze the Operational Efficiency of Taiwan Biotechnological Industry - Liu, Hsiang-Hsi (Asian Economic and Financial Review, 2017)
This study employs data envelopment analysis (DEA) method and Malmquist productivity index (MPI) to reexamine the change of operational efficiency for both individual firm and whole biotechnological industry. Concerning the whole industry, lower efficiency of the industry is mostly caused by pure technological inefficiency. When applying the sense of total factor productivity (TFP) index, the changes of TFP in biotechnological industry is most accounted for the efficiency changes rather than technological charges. These results benefit to biotechnology industry managers and regulators through the provision of useful guidelines for management control within the competitive biotechnological industry and market.